2017
DOI: 10.1007/s12602-017-9363-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Renal Scarring in Acute Pyelonephritis by Probiotic Therapy: an Experimental Study

Abstract: We evaluated the protective effects of probiotic administration as a prophylaxis treatment and immediately after fever onset in increasing the immune response and decreasing the renal scarring in a rat model of acute pyelonephritis. Twenty-four rats were apportioned to three groups. In GI (n = 8), the rats were injected with direct inoculation of Escherichia coli into the right kidney. In GII (n = 8), the rats received a probiotic regimen 1 month before E. coli injection and the probiotic regimen was continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, previous experimental models have been encouraging. In mice induced to exhibit pyelonephritis with E. coli injection, it was shown that the administration of Lactobacillus acidophilus and Bifidobacterium before and after sepsis significantly improved renal function and attenuated inflammation and renal fibrosis [ 40 ]. Similarly, administration of SCFAs improved renal function after AKI, which was an effect mediated by the decrease in sCr and urea levels, and it also improved the percentage of necrosis seen in kidney biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous experimental models have been encouraging. In mice induced to exhibit pyelonephritis with E. coli injection, it was shown that the administration of Lactobacillus acidophilus and Bifidobacterium before and after sepsis significantly improved renal function and attenuated inflammation and renal fibrosis [ 40 ]. Similarly, administration of SCFAs improved renal function after AKI, which was an effect mediated by the decrease in sCr and urea levels, and it also improved the percentage of necrosis seen in kidney biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…In another experimental model, AKI was induced in rats by urosepsis via E. coli inoculation. In this model, the administration of probiotics ( Lactobacillus acidophilus and Bifidobacterium ) one month before and two months after renal insult significantly attenuated the histological evidence of kidney injury ( 34 ).…”
Section: Introductionmentioning
confidence: 99%